2023
DOI: 10.1186/s12884-023-05808-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity education and prescription during prenatal care and maternal and fetal health outcomes: a quasi-experimental study

Abstract: Background Physical activity (PA) during pregnancy is associated with healthy gestational weight gain (GWG) and a reduced risk of developing gestational diabetes (GD), gestational hypertension (GHT) and fetal macrosomia. However, in Canada, less than 20% of pregnant women meet PA recommendations. This study assessed associations between an intervention including PA education by prenatal nurses and a PA prescription delivered by physicians and fetal and maternal outcomes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…The observed effects follow the realization of targeted interventions, which are the best strategy for enhancing health behavior among pre-pregnancy women (Pinar et al, 2020;Saidi et al, 2023). These findings point out, therefore, the possible outcome of interventions in academic institutions, mostly in female college students, and, as well, they are added to the available literature on preconception health promotion.…”
Section: Comparison the Preconception Health Behaviors Of Female Coll...supporting
confidence: 53%
“…The observed effects follow the realization of targeted interventions, which are the best strategy for enhancing health behavior among pre-pregnancy women (Pinar et al, 2020;Saidi et al, 2023). These findings point out, therefore, the possible outcome of interventions in academic institutions, mostly in female college students, and, as well, they are added to the available literature on preconception health promotion.…”
Section: Comparison the Preconception Health Behaviors Of Female Coll...supporting
confidence: 53%
“…In the analysis by Findley et al (45), women with a history of pregnancy reported that family members and partners advised them to stop exercising during pregnancy and offered them advice, leading them to a perceived a lack of ownership of their bodies. Studies have shown that well designed lifestyle counselling, provided as part of routine care, leads to improvements in the PA patterns in pregnant women (46)(47)(48), and should therefore be a mandatory part of all antenatal and obstetric consultations.…”
Section: Discussionmentioning
confidence: 99%